Candida albicans Biofilm Inhibition by Ethnobotanicals and Ethnobotanically-Synthesized Gold Nanoparticles - Judan Cruz, Khristina G.; Alfonso, Eleonor D.; Fernando, Somar Israel D.; Watanabe, Kozo (Frontiers in Microbiology, 2021)
The virulence and drug resistance of globally prevalent Candida albicans has presented complications toward its control while advances in effective antivirulence drugs remain critical. Emerging methods are now being evaluated to facilitate development of novel therapeutic approaches against this pathogen. This study focuses on the biofilm formation inhibition of ethnobotanical crude extracts and the use of nanotechnology through the ethnobotanically-synthesized gold nanoparticles to control C. albicans. Control on biofilm formation was compared using crude extracts (CEs) and biologically synthesized gold nanoparticles (CEs + AuNPs). Significantly lower biofilm formation was exhibited in thirteen (13) CEs and fourteen (14) CEs + AuNPs. Biofilm-linked genes Bcr1 and HSP90 expression were consequently downregulated. Higher biofilm inhibition activity was noted in some CEs + AuNPs compared to its counterpart CEs. This study emphasizes the biofilm inhibition activity of ethnobotanicals and the use of nanoparticles to enhance delivery of compounds, and points to its prospects for developing anti-pathogenic drugs without evolving resistance.